Pengembangan Aplikasi Pengelolaan Pondok Pesantren berbasis Web (Studi Kasus: Pondok Pesantren Nurul Islam Mojokerto) - Nurul Qomariah; Agi Putra Kharisma; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Data management at the Nurul Islam Islamic Boarding School includes violations students, permits, and also the progress of the takhossus science of students. This data management process is still uses manually by recording it on paper. This of course has the risk of losing data which of course can hinder the boarding school and parents in monitoring students. To overcome these problems, a web-based application was built to make it easier for Islamic boarding schools to manage data and also parents in monitoring the progress of their sons and daughters. This application is built on a web platform using the waterfall method. Obtained 5 actors, 50 functional requirements and 1 non-functional requirement in the elicitation of requirements to build this application. In the design results, there are 4 designs, namely sequence diagram design, class diagram design, component design and interface design. The results of this design are then used as a reference for implementing this application which results in the implementation of program code, database implementation and interface implementation. This application was tested using 3 tests, namely unit testing, integration testing and validation testing which resulted in 100% valid. In addition, the application is tested using compatibility testing which shows that the application can be used properly using the multiple browsers tested.